Inclusion of protein hydrolysates in the diet of white seabream (Diplodus sargus) larvae: impacts on skeleton quality and larvae proteome expression - Richard, Nadège (2010)
In order to investigate the effects of dietary protein hydrolysate on larval skeleton quality and larvae proteome expression, triplicate groups of white seabream (Diplodus sargus) larvae were co-fed from first-feeding onwards with live feed and three microencapsulated diets ir differing only on the molecular weight of their protein hydrolysate fraction.